Designing and testing a solution to fill ART knowledge gaps at primary healthcare level: WhatsApp-based microlearning - Chisholm, Briony Sue (Department of Medicine, 2025)
South Africa has the world's largest antiretroviral treatment programme, with 7.7 million people on treatment in 2023. Treatment of HIV is informed by regularly updated national guidelines. Knowledge of the guidelines and ongoing training of healthcare workers (HCWs) are vital, to ensure optimal patient care. Human, financial and infrastructural challenges make ongoing training difficult. Innovative solutions are needed. In the first study, South African HCWs' knowledge of dolutegravir's drug interactions – detailed in the guidelines – was established using an anonymous online survey. Descriptive and inferential analysis was done on the 1 950 surveys received from across the country. Significant gaps in knowledge were shown: 70% of participants were aware that dolutegravir has interactions; knowledge of which drugs interact and how to adjust dosing ranged between 5.1 and 79.7%. Access to guidelines and training were positively associated with knowledge, but only 69% of respondents had access to guidelines and 56% had received training. Training was desired by 90% of respondents, with computer-based online training (51%) and cell phone-based training (41%) being the preferred methods. The second study, a pragmatic, mixed-methods, parallel-group cluster-randomised study aimed to close the knowledge gaps by designing, testing and evaluating the effect of WhatsApp group-based microlearning for HIV training on HCWs' knowledge. Nurses and community health workers (CHWs) at 50 predominantly rural clinics in the Eastern Cape were invited to join the training at in-person recruitment visits. Uptake and participation were good: 232/293 nurses and 207/271 CHWs participated. Lessons were read within two weeks by 96% (nurses) and 88% (CHWs). Significant intervention effect on knowledge was seen, based on online knowledge questionnaires: nurses (0.5 units; p=0.0499) and CHWs (0.7 units; p=0.004). Data from focus groups noted that participants found the training acceptable and beneficial. Patient folders (n=1 083) were reviewed retrospectively to compare changes in patient care between the arms. Adjusting for pre-care differences, the intervention increased correct patient care by 21% (95% CI 10%-32%; p<0.001) in the year after the training. WhatsApp-based microlearning for HCWs is effective, highly acceptable, feasible and well- received, making it a valuable option for simple, accessible, scalable continuing education.